A complex systems model for transformative supply chains in emerging markets. Issue 1 (12th February 2019) - Yeoman, Ruth; Mueller Santos, Milena
Abstract : Purpose: Corporations operating global value chains must grapple with a multiplicity of ethical and practical considerations, most notably when value chains extend to emerging markets. Such contexts involve interactions with diverse stakeholders who possess the ability to impact supply chain performance, but who also bring conflicting needs, values and interests. The purpose of this paper is to outline a transformative model of supply chain fairness, arguing that adopting plural fairness principles and practices generates a higher fairness equilibrium which includes all affected stakeholders in the production of fairness outcomes, with consequent positive organizational and system level impacts. Design/methodology/approach: Through a philosophically informed overview of the literature on organizational fairness, the paper applies fairness to the management of supplier relations to identify the institutional features of ethically sustainable supply chains. The proposed conceptual model uses a complex adaptive systems approach (CADs), supplemented by describing the contribution of fairness norms and practices. Findings: This paper argues that a transformative approach to supply chain fairness can suggest new structures for interaction between firms, stakeholders, mediating institutions and governments. Originality/value: Emerging market supply chains are facing significant changes. Adopting a complex adaptive systems perspective upon stakeholder relationships, this paper offers insights from the theoretical literature on fairness, and proposes a normative model of supply chain fairness which accounts for both the normative and empirical aspects of relational complexity.